Relationship between participation in commercial fairs, and the performance of associated companies in Pro Olivo 2016 - 2017 - Valderrama Pérez, Lucio Walter M. (2019)
The development of this research work is focused on the relationship between the participation in trade fairs of the associated companies in Pro Olivo and its performance, period 2016 - 2017, which allows to establish how participation in trade fairs is related to performance, product promotion, competitive level and achievement of business objectives; The present research work is non-experimental at an explanatory, descriptive level, because data is obtained directly from the reality object of study according to the purpose of "the research. The area of ​​"research is framed in foreign trade, related to international fairs in the department of Tacna considered as a region that has a developed export vocation that are driven by state agencies and mainly by the Ministry of Production who comes implementing public policies to promote "exports. Likewise, "it has been observed that there is a need to improve the performance of the companies associated with Pro Olivo, which will allow improving their productivity, the quality of their products and therefore have a better offer in front of the" international markets. It is concluded that there is a direct relationship between the participation in trade fairs of the associated companies in Pro Olivo and their "performance.